CLIMATIC CHANGES: ANTHROPOGENIC INFLUENCE OR NATURALLY INDUCED PHENOMENON - Foscolos, A.E. (Bulletin of the Geological Society of Greece, 2010)
By the end of the 18th century eminent scientists explained the climatic changes on the basis of temperature and the ensuing glacial retreat. This disturbing observation led many prominent scientists to send air balloons equipped with special devices to trap air from the lower atmosphere in order to measure CO2 concentrations. Ninety thousand (90,000) measurements were carried out at 138 locations in 4 continents between 1810 and 1961. The data indicated that atmospheric CO2 concentrations, during the 19th century varied between 290 and 430 ppm (with an average of 322 ppm for the pre-industrial period). For the 20th century, the average concentration is 338 ppm when combined with comparable CO2 measurements carried out by Mauna Loa Observatory, Hawaii, USA (1958- 2000). Measurement precision is ±3%. Based on thermometric measurements, the mean average temperature increase from 1850 to the present is 0.75o C (0.44o C/100 years) with the following fluctuations. From 1850 to 1940 the temperature increased by +0.6o C, while from 1941 to 1975 temperature dropped by -0.2o C. From 1976 to 1998, the temperature rose by +0.35o C. From 1999 to 2006 temperature increase was nil. Finally, since 2007 the Mean Annual Temperature of Earth’s surface has substantially decreased. As far as CO2 concentration in the air’s atmosphere is concerned, it has been well documented that during the Holocene Epoch there is a substantial time lag between maximum temperatures recorded during the Interglacial periods and maximum CO2 concentrations in the atmosphere. Moreover, the same time lag is documented between 1850 and 1980, where CO2 concentrations in the atmosphere lag behind the increase of temperature for more than 100 years. A parallel increase of CO2 concentrations in the atmosphere and temperature increase is observed only between 1981 and 1995. No correlation is seen thereafter. The divergence is substantial from 2003 to the present where CO2 concentrations are increased while temperatures are decreased. These interpretations exclude any correlation between atmospheric CO2 concentrations and temperature fluctuations. Hence, in order to explain the well documented climatic changes the influence of many natural climate drivers should be accepted. Key words: climatic changes, temperatures, CO2 concentrations.